From flood control to integrated water resource management : lessons for the Gulf Coast from flooding in other places in the last sixty years - Kahan, James P. (Occasional paper (Rand Corporation) ;, 2006)
The loss of life and devastation in the Gulf coast region of the United States following the hurricane season of 2005 has led to considerable debate about what should be done and not done in recovering from the damage and mitigating the consequences of future floods. This document reports the experiences of four major floods since 1948 (two in the United States, one in the Netherlands, and one in China), to draw lessons for the Gulf coast restoration effort. The authors conclude that (1) attending to history leads to mitigating the potential damage of floods even when major floods are few and.